Analyzing the Liquidity and Solvency of the Cement Industry in the Indonesian Market: Financial Challenges and Prospects - Susilowati Susilowati; Erni Yulianti; Robby Rahadi Putra (Indonesian Journal Economic Review (IJER), 2026)
This study analyzes the liquidity and solvency of cement companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period. The primary focus of the research is to identify the influence of financial ratios on the performance of cement companies, with particular attention to how liquidity and solvency ratios affect corporate stability and competitiveness in a highly competitive market. The study employs a descriptive quantitative approach, using secondary data collected from annual financial reports. The variables analyzed include liquidity ratios (Current Ratio and Quick Ratio), solvency ratios (Debt to Equity Ratio and Interest Coverage Ratio), and profitability ratios (Return on Assets and Return on Equity) as indicators of financial performance. The findings indicate that companies with strong liquidity and solvency ratios tend to maintain stable performance despite facing economic uncertainty. This study provides recommendations for cement companies to improve the management of financial ratios in order to strengthen their market position and ensure long-term operational sustainability.